A three-dimensional thermal-hydro-mechanical coupling model for simulation of fracturing driven by multiphysics. (March 2023) - Yan, Chengzeng; Zhao, Ziheng; Yang, Yu; Zheng, Hong
Abstract: Geothermal mining, nuclear waste disposal, and other projects involve rock fracturing under the multiphysics effect. There is an urgent need for a numerical analysis tool that can consider both thermal-hydro-mechanical coupling (THM) effects and rock fracturing to analyze such projects. This paper presents a three-dimensional thermal-hydro-mechanical coupling model that can consider rock fracturing, which incorporates the advantages of the combined finite discrete element method (FDEM) for simulating fracture and fragmentation. The 3D thermal-hydro-mechanical coupling model includes three parts: fracture-pore mixed seepage model, heat transfer model (including heat conduction in solid and fluid, heat advection, heat exchange between solid and fluid), and FDEM fracture mechanics calculation model. Some examples with the analytical solution for seepage, hydromechanical, thermal–mechanical, hydrothermal, and thermal-hydro-mechanical coupling problems are used to verify the correctness of the FDEM based 3D THM model in detail. In addition, an example of rock fracturing caused by the thermal-hydro-mechanical coupling effect is also given. The simulation results show that the FDEM based 3D thermal-hydro-mechanical coupling model can simulate the complex fractures initiation, propagation, and extension caused by multiphysics effects, such as heat, fluid, and mechanics.